Strategi Komunikasi Public Relations saat Magang Mahasiswa UINSU di Biro Administrasi Pembangunan Kantor Gubernur SUMUT - Hasan Sazali; Wandra Adhira; Nova Natasha (CV. ITTC INDONESIA, 2025)
This research analyzes the public relations communication strategies implemented by the Development Administration Bureau at the North Sumatra Governor's Office during field work practices (PKL). PKL provides an opportunity for students to understand communication management between government and society. Using qualitative methods with a case study approach, this research collects data through in-depth interviews, observations and documentation studies related to communication policies. The research results show that the communication strategy used involves two-way communication, effective use of social media, and application of the principle of transparency in every communication activity. This approach helps increase public engagement and strengthen people's trust in government. It is hoped that these findings can contribute to the development of more effective public relations communication strategies in government, especially at the provincial level, in order to improve harmonious relations between government and society.